(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Culture media is one useful aspect for the development of microalgae. Adding fertilizer to the culture media can affect the density of Chlorella sp. When carrying out culture, it is necessary to have liquid organic fertilizer (POC) which is easy to obtain and found in nature, especially liquid organic fertilizer made from a fermented mixture of rice water, coconut water and eco enzymes. This research seeks to determine the effect of density of Chlorella sp. by administering liquid organic fertilizer made from rice water, coconut water and Eco enzyme fermentation, we can find out the ideal dose needed for the growth of chlorella sp. The highest throughout the study was obtained in treatment A (dose of 5 ml eco enzyme), which was followed by treatment C (does 12 ml/l POC + 2 ml/l eco enzyme), treatment B (does 8 ml/l POC + 2 ml/l eco enzyme), and the lowest in treatment D (dose 16 ml/l POC + 2 ml/l eco enzyme). Providing liquid organic fertilizer with rice washing water and coconut water had a significant effect on density of Chlorella sp. (p value <0.05). The highest density occurred on day 6 in treatment C, where a mixture of rice washing water and coconut water containing 5 ml of eco enzyme produced a population density of 6996.67 x 104 cells/ml.